Sol-gel synthesis and characterization of Sr/Mg, Mg/Zn and Sr/Zn co-doped hydroxyapatites - Kaygili, Omer; Keser, Serhat (Elsevier Science Bv, 2015)
In the present work, a series of hydroxyapatite (HAp) samples co-doped with Sr/Mg, Mg/Zn, and Sr/Zn were synthesized using sol-gel method. The formation of the HAp phase was found to be in the range of 93.0-97.4%. Compared to the undoped HAp, with increasing amount of the co-dopants, a gradual decrease in the values of the crystallinity percent, lattice parameters and volume of the unit cell decrease were observed. B-type carbonate substitution was detected for all the samples. All the samples had the morphology consisting of the nanoparticles. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bioceramics; Crystal structure; Sol-gel preparation; X-ray techniques; Electron microscopy